JEJAK PENAFSIRAN RASIONAL PADA KITAB TAFSIR JUZ ‘AMMA KARYA MUHAMMAD ABDUH - Firmansyah, Rizki; Bosu, Sufian (MIMESIS, 2023)
Muhammad Abduh is a reformer who is known for the renewal of Islamic thought in various fields. Muhammad Abduh is often aligned with mu'tazilah in the rationality of his thoughts, for him, reason and revelation should not be separated and should not be clashed because both can be used as clues for humans. This basis then became the footing of Abduh's thought in both interpretations, one of which was the interpretation of juz amma. This research is qualitative research with a text analysis approach, the main source of this study is the interpretation of juz amma Muhammad Abduh. The conclusion of this study was found that the interpretation of juz amma Muhammad Abduh has an element of rationality of science and language even with a limited number.